BMP9-induced osteoblastic differentiation requires functional Notch signaling in mesenchymal stem cells - Cui, Jing (Lab Invest, 2018)
Mesenchymal stem cells (MSCs) are multipotent progenitors that can differentiate into multiple lineages including osteoblastic lineage. Osteogenic differentiation of MSCs is a cascade that recapitulates most, if not all, of the molecular events occurring during embryonic skeletal development, which is regulated by numerous signaling pathways including bone morphogenetic proteins (BMPs). Through a comprehensive analysis of the osteogenic activity, we previously demonstrated that BMP9 is the most potent BMP for inducing bone formation from MSCs both in vitro and in vivo. However, as one of the least studied BMPs, the essential mediators of BMP9-induced osteogenic signaling remain elusive. Here we show that BMP9-induced osteogenic signaling in MSCs requires intact Notch signaling. While the expression of Notch receptors and ligands are readily detectable in MSCs, Notch inhibitor and dominant-negative Notch1 effectively inhibit BMP9-induced osteogenic differentiation in vitro and ectopic bone formation in vivo. Genetic disruption of Notch pathway severely impairs BMP9-induced osteogenic differentiation and ectopic bone formation from MSCs. Furthermore, while BMP9-induced expression of early-responsive genes is not affected by defective Notch signaling, BMP9 upregulates the expression of Notch receptors and ligands at the intermediate stage of osteogenic differentiation. Taken together, these results demonstrate that Notch signaling may play an essential role in coordinating BMP9-induced osteogenic differentiation of MSCs.